ANALISIS DESAIN POROS DAN DOCTA EKSENTRIK UNTUK GEARBOX ROTOGRAVURE MENGGUNAKAN METODE ELEMEN HINGGA - Bagus Adi Prasetyo; Heri Yudiono (Scientific Journal of Mechanical Engineering Kinematika, 2022)
The design of the eccentric shaft and docta of the rotogravure gearbox must have the correct design structure construction and material type so as to increase the effectiveness and efficiency of the gearbox performance. The purposes of this study is to determine the safest and optimum eccentric shaft and docta design based on the results of analysis on the CATIA V5 software simulation. This study uses the finite element method by analyzing the structure of the shaft and docta eccentric components in the form of von Mises stress values, displacements, and safety factor calculations which are displayed in color contours. The eccentic shaft design with the lowest von Mises stress value has a value of 178,92 MPa, the lowest displacement value is 0,22042 mm, and the highest safety factor calculation results is 2,505. Meanwhile, the consequences of the eccentric docta design analysis with the lowest von Mises stress value have a value of 24,92 MPa, and the lowest displacement value is 0,021661 mm, and the highest safety factor calculation result is 18,45. It was concluded that the eccentric shaft design 4 and eccentric docta 4 using ST 60 material resulted in the lowest von Mises, the lowest displacement, and the most highest safety factor value calculation compared to other eccentric shaft and docta designs so that this new design is the safest and optimum design for the loading model that occurs.